Infusing reflective practice in eLearning courses – can widgets help?. (16th March 2011) - Verpoorten, Dominique; Westera, Wim; Specht, Marcus
The paper investigates the potential of using widgets-based reflection amplifiers in e-learning courses. Reflection amplifiers are structured opportunities for students to examine and evaluate aspects of their learning experience. The paper deliberately chooses a non-technical viewpoint. It takes the teachers' voices as a starting point. The study reports the results of a survey that asked open educational resources (OERs) course creators about their opinions on different types of reflection amplifiers. The outcomes demonstrate that several reflection techniques are recognised and acknowledged by these practitioners as being of relevance for their courses. Yet, practical application in their courses is quite rare. Results of the survey are subsequently used to inspect possible contributions of widgets technology to the implementation and dissemination of a selection of reflection techniques. The set-up of an experiment intended to test feasibility and relevance of widgets-based reflection amplifiers is eventually outlined.